1996
DOI: 10.1002/j.1460-2075.1996.tb00398.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin blocks the phosphorylation of 4E-BP1 and inhibits cap-dependent initiation of translation.

Abstract: The immunosuppressant drug rapamycin blocks progression of the cell cycle at the G1 phase in mammalian cells and yeast. Here we show that rapamycin inhibits cap‐dependent, but not cap‐independent, translation in NIH 3T3 cells. Cap‐dependent translation is also specifically reduced in extracts from rapamycin‐treated cells, as determined by in vitro translation experiments. This inhibition is causally related to the dephosphorylation and consequent activation of 4E‐BP1, a protein recently identified as a repress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
574
3
7

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 640 publications
(619 citation statements)
references
References 39 publications
30
574
3
7
Order By: Relevance
“…However, the magnitude of the decrease in response to etoposide was greater than that caused by rapamycin, which, like etoposide, causes inhibition of p70 S6 kinase and dephosphorylation of 4E-BP1. These data are in line with those for other cells, where treatment of serum-fed cells with rapamycin generally only causes a modest inhibition of total protein synthesis, especially at early times (see, e.g., (Beretta et al, 1996;Morley et al, 1998)). It thus seemed likely that etoposide interfered with other steps in mRNA translation in addition to those regulated through mTOR, and we therefore extended our analysis to include two proteins which are known to play key roles in regulating overall protein synthesis, eIF2 and eIF2B.…”
Section: Etoposide Treatment Inhibits Protein Synthesissupporting
confidence: 89%
“…However, the magnitude of the decrease in response to etoposide was greater than that caused by rapamycin, which, like etoposide, causes inhibition of p70 S6 kinase and dephosphorylation of 4E-BP1. These data are in line with those for other cells, where treatment of serum-fed cells with rapamycin generally only causes a modest inhibition of total protein synthesis, especially at early times (see, e.g., (Beretta et al, 1996;Morley et al, 1998)). It thus seemed likely that etoposide interfered with other steps in mRNA translation in addition to those regulated through mTOR, and we therefore extended our analysis to include two proteins which are known to play key roles in regulating overall protein synthesis, eIF2 and eIF2B.…”
Section: Etoposide Treatment Inhibits Protein Synthesissupporting
confidence: 89%
“…5D). Inhibition of mTOR signaling often induces a G1 cell cycle arrest that correlates with down-regulation of cyclin D1 levels in some cell types (Beretta et al, 1996). We found that metformin induced G1 cell cycle arrest and decreased levels of cyclin D1.…”
Section: Discussionmentioning
confidence: 60%
“…Hypophosphorylated 4E-BP1 inhibits translation initiation by binding to eIF4E with high affinity. The binding of 4E-BP1 to eIF4E prevents the formation of the eIF4F complex, which is the rate-limiting step in translation initiation (Beretta et al, 1996). Metformin also induced phosphorylation of AMPK (T172) (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…The experiment was carried out three times and the error bars represent standard errors of the mean dissociation of their complexes with eIF4E (Sonenberg, 1996; Lawrence and . The pathway leading to these events is inhibited by rapamycin, due to impairment of the phosphorylation of the 4E-BPs Beretta et al, 1996a). In BJAB cells overall protein synthesis is particularly sensitive to rapamycin (Kay et al, 1996), suggesting that the e ects of the drug are not limited to the translation of mRNAs with 5' terminal oligopyrimidine tracts (Je eries et al, 1994; in this system.…”
Section: Is Inhibition Of Protein Synthesis Su Cient To Destabilize Ementioning
confidence: 92%
“…The extent of complex formation between the best studied of these proteins, 4E-BP1 (also known as PHAS-I) (Lawrence and , and eIF4E is regulated by the phosphorylation of 4E-BP1 (Graves et al, 1995;Von Manteu el et al, 1996;Brunn et al, 1997). This phosphorylation is activated by a pathway which can be inhibited by the macrolide immunosuppressant, rapamycin Von Manteu el et al, 1996;Beretta et al, 1996a;Fadden et al, 1997;Brunn et al, 1997). As a result rapamycin inhibits cap-dependent initiation (Beretta et al, 1996a,b), as well as antagonizing increases in protein synthesis brought about by mitogenic stimuli .…”
Section: Introductionmentioning
confidence: 99%